Mental Health Links With Eating Disorder Risk and Weight Related Concerns in First Semester College Students. (7th June 2021) - Yu, Zhiping; Fuglestad, Paul; Reasonover, Madisen
Abstract: Objectives: Both mental health and eating disorders are increasing health concerns for college students. This study aimed to examine associative links between psychological distress, eating disorder risk, food addiction, and weight related concerns among first semester college students. Methods: Freshman students 18 years or older in all majors in a southeastern university were invited to take an online survey. The measures included demographic characteristics, psychological behaviors and eating disorder risks. Pearson's correlation analysis was used to assess associations. Results: Ninety-two students (79.3% female, 61.5% white) completed the survey. Psychological distress significantly correlated with higher eating disorder risk (stress r = 0.28, anxiety r = 0.28, depression r = 0.42; P 's < 0.01), higher food addiction symptom count (stress r = 0.30, anxiety r = 0.34, depression r = 0.44; P 's < 0.01), and lower weight related quality of life (stress r = −0.27, anxiety r = −0.38, depression r = −0.52; P 's < 0.01). Greater anxiety also significantly correlated with lower self-reported dream weights ( r = −0.23, P < 0.05) and happy weights ( r = −0.23, P < 0.05). Conclusions: The findings suggest that the management of psychological well-being of college students is important for prevention and treatment of eating disorders and weight issues in this population. Funding Sources: Brooks College of Health, University of North Florida.